Media Pembelajaran Computer Base Training (CBT) Menggunakan Aplikasi Adobe Animate CC Mata Kuliah Sistem Manajemen Keselamatan dan Kesehatan Kerja - Wawan Riyanta (Universitas Lambung Mangkurat, 2023)
Computer-based training is a teaching material that can support distance lectures that demand more interesting, attractive, and efficient media. The creation of CBT learning media is carried out using the research and development (R&D) method, which involves making and testing or verifying applications and testing the applications' effectiveness. The development and manufacture of CBT media products uses the Adobe Animate CC platform, and then a feasibility test is carried out using a validation questionnaire using a Likert scale that will be carried out by the validator. Evaluation of educational media Products to 54 respondents and processing the results of the assessment from users obtained very good results with a value of 3.96 and a percentage of 79.3%, with details of the assessment of each sub-element of the software engineering aspect of 92%, the learning design aspect of 86%, and the visual communication aspect of 48%. The visual communication aspect has the lowest assessment result from the other two aspects, with three of its subaspects falling into the inappropriate category, namely audio, moving media, and interactive layout. The results of this research will become an interactive teaching platform for PPI lecturers in 2022.Keyword: Covid-19, Media, CBT, K3, Annimate CC